Guidance and Counseling Services for Students with Special Needs in Inclusive Education Schools in the DKI Jakarta Region - Marja Marja (Department of Special Education, 2025)
Educational services for children with special needs or students with disabilities, currently in its implementation has changed from what was previously implemented in special schools, developing in a general/regular school setting known as an inclusive school. The basic principle in inclusive education is that the implementation of education is based on the special needs and individual differences in a regular education setting. Guidance and counseling services for children with special needs are greatly needed, both in special schools and in inclusive schools. The education process at school will certainly experience many problems in learning, social interaction, accessibility, and provision of human resources. These problems can be minimized by the presence of counselors in schools, both in special schools and in inclusive schools. Based on data obtained from 13 schools related to children with special needs counseling services, it is known that ABK BK services in inclusive schools, both at elementary to secondary school levels, are carried out by class teachers, counselors, and special education teachers. The existence of counseling services for children with special needs, especially in schools that provide inclusive education, ultimately needs to be prepared in line with the implementation of DKI Jakarta Governor Regulation Number 40 of 2021, when schools according to type and level accept children with special needs to study together in regular schools in an inclusive education setting.